Fibrodysplasia ossificans progressiva in Hong Kong—A case report series - Chan, Joshua Chun Ki; Kuong, Evelyn Eugenie; Chan, Joyce Pui Kwan; Luk, Ho Ming; Fung, Jasmine Lee Fong; Tung, Joanna Yuet-ling; Chung, Brian Hon Yin (Frontiers in Pediatrics, 2023)
Fibrodysplasia ossificans progressiva (FOP) is an ultra-rare condition. The diagnosis could be challenging due to its rarity and non-specific presenting symptoms. However, early diagnosis and appropriate management help in preserving patients' function and quality of life. Herein, we report the diagnostic journeys and clinical courses of 8 patients with FOP in Hong Kong and illustrate the challenges involved.